THE RELATIONSHIP BETWEEN PANCASILA AND RELIGION TO INCLUSIVISM FROM THE PROCLAMATION PERIOD TO THE PRESENT IN INDONESIA - Simanungkalit, Josua Chariston; Manalu, Maria Magdalena; Simanungkalit, Pebriyan (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research aims to analyze the relationship between Pancasila and religion in shaping and strengthening inclusivism in Indonesia, from the proclamation period to the contemporary era. Using a descriptive qualitative approach, data was collected through literature studies, historical documentation, and interviews with religious leaders and academics. The results of the study show that since the beginning of independence, Pancasila has been formulated as the basis of an inclusive state and able to accommodate religious diversity through the precepts of the One Godhead. The state plays an active role in strengthening inclusivity through official religious recognition policies, the establishment of the Forum for Religious Harmony (FKUB), and multicultural education. Social practices such as interfaith dialogue and joint religious celebrations reflect the application of Pancasila values in daily life. However, this study also found challenges such as increasing intolerance, radicalism, and identity politics that hinder the spirit of togetherness. Therefore, strengthening inclusivism requires synergy between the state and society through the internalization of Pancasila values, religious moderation, and the strengthening of the law against discriminatory actions. This research emphasizes that Pancasila and religion are not entities that contradict each other, but complement each other in realizing a just, peaceful, and harmonious society.